НОРМАТИВНО-ПРАВОВЕ РЕГУЛЮВАННЯ ДІЯЛЬНОСТІ З ОРГАНІЗАЦІЇ ТА ПЛАНУВАННЯ РОЗСЛІДУВАННЯ КРИМІНАЛЬНИХ ПРАВОПОРУШЕНЬ У ПЕРІОД «МОДЕРНІЗАЦІЇ» ІНСТИТУТУ ДОСУДОВОГО РОЗСЛІДУВАННЯ ТА СИСТЕМИ ОРГАНІВ ДОСУДОВОГО РОЗСЛІДУВАННЯ - Татарин, Назарій Миколайович (SUPREMANCE OF LAW, 2018)
The article emphasizes that the investigation of criminal offenses is an activity of authorized subjects clearly regulated by the criminal procedural legislation of Ukraine. It is noted that the organizational aspects of their functioning are quite often regulated by normative legal acts of the sub-legal level. It is emphasized that the determination of the conceptual foundations of the organization and planning of the investigation of criminal offenses is considered impossible without clarifying the genesis of the regulatory and legal regulation of the specified activity. It has been found that the genesis of the legal regulation of the organization and planning of the investigation of criminal offenses is determined taking into account the periods significant for the formation and reform of the pre-trial investigation system in independent Ukraine, guided by the features of the transition from a totalitarian regime to a democratic, market transformation of the economy, changes in system, functions and powers of law enforcement agencies, including those related to combating criminal illegal activities. Such a period in the regulatory and legal provision of pre-trial investigation of criminal offenses in general and the organization and planning of investigations in particular is singled out and characterized as a period of “modernization” of the institution of pre-trial investigation and the system of pre-trial investigation bodies. The specified period is from 04.12.2012 to the present time. It was found that the Criminal Procedure Code of Ukraine was adopted during this period; in connection with the reform of the law enforcement sphere, the system of pre-trial investigation bodies underwent significant changes: the prosecutor’s office system was reorganized and “the powers of the prosecutor to perform the functions assigned to him” were changed; the police and tax police were abolished; the National Police, the State Bureau of Investigation, the Bureau of Economic Security of Ukraine were created; the organization of the judiciary and the administration of justice in Ukraine has changed.
Keywords: legal regulation; institute of pre-trial investigation; criminal procedural activity; legal acts; organization of investigation; planning of investigation; genesis; formation; development; period of “modernization” of institute of pre-trial investigation and system of pre-trial investigation bodies